PENGARUH MEKANISME CORPORATE GOVERNANCE DAN STRUKTUR KEPEMILIKAN PUBLIK TERHADAP LUAS PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT - Barbara Gunawan (KRISNA: Kumpulan Riset Akuntansi, 2020)
This research aims to examine the effect of corporate governance mechanisms and the structure of public ownership on the broad disclosure of enterprise risk management in manufacturing companies in Indonesia and Malaysia. The sample in this study were manufacturing companies listed on the Indonesia Stock Exchange and Malaysia Stock Exchange in the period 2015 - 2017. This study uses secondary data. Data collection techniques used purposive sampling method and obtained 183 samples in Indonesia and 180 samples in Malaysia. This research use SPSS version 15.0 as data analysis tool. The results of the analysis obtained indicate that the Independent Commissioner, the reputation of the auditor, and the size of the company have a positive effect on the broad disclosure of enterprise risk management. While the number of members of the board of commissioners and the structure of public ownership negatively affected the broad adoption of enterprise risk management in Indonesian manufacturing companies. the results of the analysis of Independent Commissioners, the number of members of the board of commissioners, and the reputation of the auditor have a positive effect on the broad disclosure of enterprise risk management. While the size of the company and the structure of public ownership negatively affect the Broad Disclosure of Enterprise Risk Management in manufacturing companies in Malaysia.